A Cross-Sectional Study on the Risk Factors of Overnutrition Status among Junior High School Students - Ayuningtyas, Dyah; Arini, Firlia Ayu; Fauziyah, A'immatul; Nasrulloh, Nanang (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2025)
Abstract Background: Overweight status in adolescents is known to have a high prevalence and continues to grow every year. This trend increased by 5.2% among adolescents aged 13-15 in Indonesia, and the Bekasi Regency has the fourth highest prevalence in West Java Province. Over time, changes in the quality and quantity of diet and lifestyle can be a factor in the occurrence of overweight status in adolescents. This study aims to determine the relationship between ultra-processed food consumption habits, physical activity, and sleep duration with overweight status in adolescents at Junior High School 1 South Tambun. Method: This study used an analytic observational method with a cross-sectional design. The study population comprised 160 students in grades 7 and 8 at State Junior High School 1 South Tambun, and a sample of 113 respondents using a stratified random sampling technique. Research data were obtained directly through anthropometric measurements and filling out questionnaires. Data were analysed using univariate and bivariate analysis with the Chi-Square statistical test. Result: The percentage of overnutrition status in adolescents was 28.3%. Based on data analysis through the Chi Square test, the relationship between ultra-processed food consumption habits and overweight status (p=0.270), physical activity and overweight status (p=0.306), and sleep duration with overweight status (p=0.771). Conclusion: Consumption habits of ultra-processed foods, physical activity, and sleep duration are not associated with overweight among Junior High School 1 South Tambun adolescents. The high percentage of overnutrition status in this study suggests that adolescents should adopt a healthy diet and lifestyle to prevent an increase in the prevalence of overnutrition status.